Molecular encapsulator on the surface of magnetic nanoparticles. Controlled drug release from calcium Ferrite/Cyclodextrin–tethered polymer hybrid - Ramasamy, Sivaraj; Samathanam, Beniya; Reuther, Helfried; Adyanpuram, Muthukumar Nadar Meenakshi Subbaraman; Enoch, Israel Vijayaraj Muthu Vijayan; Potzger, Kay (Colloids and surfaces, B, Biointerfaces, 2018)
[Display omitted] •75 nm-sized calcium ferrite nanoparticles are prepared as drug delivery agents.•The β-Cyclodextrin–tethered dextran-coated nanoparticles are loaded with camptothecin.•Cytotoxicity on human cervical cancer cells is studied.•The toxicity of the nanoparticles on brine shrimp, Artemia salina, is reduced on the polymer coating. Magnetic nanoparticles (MNPs) are intriguing due to their potency to deliver anti-cancer drugs. This paper presents the inference from our experimental attempts to add merit to the concept of magnetic drug carrier, by designing calcium ferrite nanoparticles and coating them with a biocompatible dextran tethered with a hydrophobic cavity-containing molecule, β-cyclodextrin (β-CD). The size, crystal system, and the morphology of the MNPs are studied. The magnetic properties are explored using vibrating sample magnetometry, SQUID and Mössbauer spectroscopy. The roughly 75nm MNPs, encapsulated with the β-CD–dextran conjugate allows a slow and sustained in vitro release of the loaded anti-cancer drug, Camptothecin, from the polymer shell. The study of cytotoxicity reveals that the loaded Camptothecin retains its potency as efficient as an effective carrier of the anti-cancer drug. Further, the toxicity of the nanomaterial is tested on an organism which is highly sensitive to toxicity i.e., brine shrimp (Artemia salina). The polymer coating brings down the toxicity of the MNPs.